Q: 9a plus 8 minus 2a minus 3 minus 5a?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

2a+5

2a+5a+9a = 16a

9a +8 -2a -3 -5a = 2a +5

9a +8 -2a -3 -5a = 2a +5

9a +8 -2a -3 -5a = 2a +5

4a2 - 9a + 5 = 4a2 - 4a -5a + 5 = 4a(a - 1) - 5(a - 1) = (4a - 5)(a - 1)

a + 3a + 5a = 180 9a =180 a = 20

9a + 1

9a + 3b - 11a - 4b = -2a -b

It is the same as: 9a -4a = 5a

In order to solve something, there needs to be an equation. If I have read your equation right you have: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) This looks like it needs to be simplified. There are two fractions being multiplied, so multiply the numerators and denominators together, giving: (a² - 4)/(2 + 6a) x (3 + 9a)/(a² + 5a + 6) = ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) Now, simplify the polynomials to remove the squared terms and any common factors: a² - 4 = (a - 2)(a + 2) 2 + 6a = 2(1 + 3a) 3 + 9a = 3(1 + 3a) a² + 5a + 6 = (a + 3)(a + 2) Giving: ((a² - 4)(3 + 9a)) / ((2 + 6a)(a² + 5a + 6)) = ((a + 2)(a - 2)3((1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) This can now be simplified by cancelling out equivalent terms, giving: ((a + 2)(a - 2)3(1 + 3a))/(2(1 + 3a)(a + 3)(a + 2)) = ((a - 2)3) / (2(a+3)) = 3(a - 2) / 2(a + 3) = (3a - 6) / (2a + 6)

4a - 2.1 = 9a + 5.4 4a - 9a = 5.4 +2.1 -5a = 7.5 -a = 1.5 a = -1.5